Force Measurement Using Zero-Compliance Mechanism - Takeshi Mizuno; Yuji Ishino; Hiroki Kawada; Yoichiro Hayashi; Masaya Takasaki; Masayuki Hara; Daisuke Yamaguchi (SICE Journal of Control, Measurement, and System Integration, 2018)
Force measurement using zero-compliance mechanism is proposed and studied experimentally. A zero-compliance mechanism is composed of two suspensions connected in series; one of them is operated to cancel the deflection of the other so that the total length of the suspension is maintained even if force acts between the ends. In the proposed measurement system, one of the ends becomes the point of force and the point of the connection becomes the detection point. The force is estimated from the displacement of the detection point. An apparatus is fabricated for experimental study to show the validity of the proposed measurement method. Double series magnetic suspension is used to achieve zero compliance. In the apparatus, the motions of two suspended objects (floators) are controlled with a single electromagnet. Each floator is supported by leaf springs to move in the vertical direction translationally. The attractive force of the electromagnet directly acts on the first floator in which a permanent magnet is installed. The motion of the second floator is controlled indirectly through the attractive force of the permanent magnet. To achieve the zero compliance characteristic, PID control is applied to the second floator. It is confirmed experimentally that the deflection of the second suspension, i.e., the distance between the first and second floators, is proportional to external force acting on the second floator. This result indicates that the force can be estimated for the deflection of the second suspension. It is also demonstrated that dynamic force can be measured by the proposed method.